Micro-craters in muddy tidal flats of cold regions - Dionne, Jean-Claude (Cahiers de géographie du Québec, 1972)
Meltwaters dripping from overhanging ice cakes, stranded at low tide on muddy tidal flats of the St.Lawrence Estuary, near Québec City, cause micro-craters to form on soft mud and silty-sand sediments. The shallow depressions are circular, symmetrical, and with rims a few mm high, some have a tiny hole centered in the bottom. Craters range from 7 to 15 cm in diameter, and 20 to 50 mm in depth ; they characterize tidal flats of cold regions.